Measurement of Protein Dynamics from Site Directed Cu(II) Labeling. Issue 1 (1st September 2022) - Singewald, Kevin; Hunter, Hannah; Cunningham, Timothy F.; Ruthstein, Sharon; Saxena, Sunil
Abstract: This review describes the use of Electron Paramagnetic Resonance (EPR) to measure residue specific dynamics in proteins with a specific focus on Cu(II)‐based spin labels. First, we outline approaches used to measure protein motion by nitroxide‐based spin labels. Here, we describe conceptual details and outline challenges that limit the use of nitroxide spin labels to solvent‐exposed α‐helical sites. The bulk of this review showcases the use of newly developed Cu(II)‐based protein labels. In this approach, the strategic mutation of native residues on a protein to generate two neighboring Histidine residues (i.e., the dHis motif) is exploited to enable a rigid site‐selective binding of a Cu(II) complex. The chelation of the Cu(II) complex to dHis directly anchors the Cu(II) spin label to the protein backbone. The improvement in rigidity expands both the spin‐labeling toolkit as well as the resolution of many EPR measurements. We describe how EPR measurements of the Cu(II) label directly reflect backbone motion and fluctuations. The EPR are complemented by Molecular Dynamics simulations. Finally, the dHis motif provides access to the measurement of site‐specific dynamics at both α‐helices and β‐sheets. The review outlines the limitations of the dHis method and provides an outlook for future developments. Abstract : Site‐specific protein dynamics are important for protein function and catalytic activity. Electron paramagnetic resonance (EPR) combined with site‐directed spin labeling is an incisive tool to measure these site‐specific fluctuations. In particular, Cu(II) labeling strategies allow direct observation of backbone dynamics for both α‐helical and β‐sheet sites. This review provides a comprehensive description on the role Cu(II) labeling plays in comparison to commonly used nitroxide labels as well as how dynamics is interpreted from Cu(II) lineshapes.